Influence of regional organizations on consumers preferences: The dairy market of Eurasian Custom Union - Ali, Shaukat; Utev, Sergey (Journal of Eastern European and Central Asian Research (JEECAR), 2016)
The establishment of the Eurasian Custom Union created a common market in Russia, Belorussia and Kazakhstan and increased trade flows among the countries. Elimination of trade barriers among countries of the union changed the market landscape due to on one hand, the producers from the countries achieving competitive advantages against producers from countries outside the union; on the other hand, competition within the union increased. These changes in turn impact purchasing habits of consumers. This paper explores the influence of regional integration on consumer attitudes toward domestic products. A survey was conducted to examine consumer attitudes toward domestic and foreign dairy products in markets of Russia, Kazakhstan and Belorussia before and after the establishment of Eurasian Custom Union. The survey also compared the influence of the Eurasian Custom Union on the attitude of consumers from different social groups segmented by gender, age, country of residence, income level and ethnic belonging. The results of the survey reveal that there were some differences in perception of changes in diversity of dairy products by consumers from different ethnic groups but it was not statistically significant.